Metamaterial Absorbers: From Tunable Surface to Structural Transformation. Issue 38 (22nd August 2022) - Li, Weiwei; Xu, Manzhang; Xu, He‐Xiu; Wang, Xuewen; Huang, Wei
Abstract: Since the first demonstration, remarkable progress has been made in the theoretical analysis, structural design, numerical simulation, and potential applications of metamaterial absorbers (MAs). With the continuous advancement of novel materials and creative designs, the absorption of MAs is significantly improved over a wide frequency spectrum from microwaves to the optical regime. Further, the integration of active elements into the MA design allows the dynamical manipulation of electromagnetic waves, opening a new platform to push breakthroughs in metadevices. In the last several years, numerous efforts have been devoted to exploring innovative approaches for incorporating tunability to MAs, which is highly desirable because of the progressively increasing demand on designing versatile metadevices. Here, a comprehensive and systematical overview of active MAs with adaptive and on‐demand manner is presented, highlighting innovative materials and unique strategies to precisely control the electromagnetic response. In addition to the mainstream method by manipulating periodic patterns, two additional approaches, including tailoring dielectric spacer and transforming overall structure are called back. Following this, key parameters, such as operating frequency, relative tuning range, and switching speed are summarized and compared to guide for optimum design. Finally, potential opportunities in the development of active MAs are discussed. Abstract : Metamaterial absorbers (MAs), designed using artificial subwavelength structures, feature low profile and unique absorption. Employing active components into the element designs facilitate multifunction and miniaturization of MAs. A comprehensive and systematical review covering the work essentially conducted in the domain of cutting‐edge active MAs is presented, highlighting innovative materials and unique strategies to manipulate electromagnetic response at frequencies up to optical regions.